A Mathcad‐based educational experience to address the design of nonisothermal plug flow reactors. Issue 4 (28th March 2022) - Cuadri, Antonio A.; Gallego, Rocío; Martín‐Alfonso, María J.; Delgado‐Sánchez, Clara; Cortés‐Triviño, Esperanza; Tenorio‐Alfonso, Adrián; Borrero‐López, Antonio M.; Ortega, Francisco J.
Abstract: Mathcad is a simple‐to‐use and intuitive mathematical software that helps students to minimize the mathematical difficulties involved in solving engineering problems. The design of nonisothermal plug flow reactors (PFR) is a fundamental issue within the field of chemical reaction engineering; however, its teaching–learning process is hindered by students' mathematical difficulties in solving ordinary differential equations. In this paper, the software Mathcad was conveniently integrated into an educational experience through the resolution of two real case studies. In the first one, a simple liquid‐phase reaction is considered in a PFR working at different operating conditions, whereas the second case evaluates a PFR taking place multiple reactions (parallel reactions) with a heat exchanger attached. The assessment of this experience, which was held into two 5‐h Mathcad workshops, revealed that Mathcad made the design of non‐isothermal PFR more appealing, facilitated the understanding of the design process, and brought another dimension to the way the students perform complex calculations.